Implementasi Sistem Keuangan Desa (Siskeudes ) Dalam Pengelolaan Anggaran Pendapatan Dan Belanja Desa (Apbdes) Di Desa Kodon-Kodon Kecamatan Merek Kabupaten Karo - Ardy Rohan Liharman Sinaga; Marlon Sihombing; Humaizi Humaizi (PERSPEKTIF, 2022)
The purpose of this paper is to analyze the Implementation of the Village Financial System (Siskeudes) and the Inhibiting Factors in the Implementation of the Village Financial System (Siskeudes) in the Management of the Village Revenue and Expenditure Budget (Apbdes) in Kodon-Kodon Village, Brand District, Karo Regency. The research method used in this research is descriptive research with a qualitative approach with the subject of key informants and additional informants. In 2020 SISKEUDES Application Version 2.0. The theory of implementation used is the theory of implementation of the George C. Edward III Model. The results of the study indicate that the transparency in reporting village financial management is quite good, in terms of the existing resources in the village that are able to operate the SISKEUDES application, which is still very limited. Technical implementers in operating the SISKEUDES application are often negligent in carrying out their duties in the SISKEUDES application. The bureaucratic structure is still less effective between the Village Head and the Technical Implementer of the SISKEUDES Application. The village head must wait for the results of the financial reports prepared by the technical implementer of the SISKEUDES APP.